Battery cell, battery device, power consuming device, and method for producing composite positive electrode active material
Patent Information
- Application Number
- CN202510569913.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]电池在实际作业时,一些体系例如三元正极活性材料等在高压条件下会加速晶格释氧,由此导致过渡金属溶出及晶型转变;此外过度脱锂也会导致结构坍塌,晶体结构受到应力增加并出现晶间及晶内的裂隙;高电压也会加剧电解液与正极材料间副反应;以上问题会影响电池在高电压下循环性能
[0048]上述说明仅是本申请技术方案的概述,为了能够更清楚了解本申请的技术手段,而可依照说明书的内容予以实施,并且为了让本申请的上述和其它目的、特征和优点能够更明显易懂,以下特举本申请的具体实施方式。
Smart Images

Figure CN123017870A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to a method for preparing a battery cell, a battery device, an electrical device, and a composite positive electrode active material. Background Technology
[0002] During actual operation, some systems, such as ternary cathode active materials, will accelerate the release of oxygen from the lattice under high voltage conditions, which will lead to the dissolution of transition metals and crystal transformation. In addition, excessive delithiation will also cause structural collapse, increased stress on the crystal structure and the appearance of intergranular and intragranular cracks. High voltage will also exacerbate the side reactions between the electrolyte and the cathode material. The above problems will affect the cycle performance of the battery under high voltage.
[0003] Therefore, it is crucial to develop a battery cell that exhibits excellent cycle performance at high voltages. Summary of the Invention
[0004] In view of the above problems, this application provides a method for preparing a battery cell, a battery device, an electrical device, and a composite positive electrode active material, wherein the battery cell has excellent cycle performance under high voltage.
[0005] In a first aspect, this application provides a battery cell, the battery cell including a positive electrode sheet;
[0006] The positive electrode includes a positive current collector and a positive film layer disposed on at least one surface of the positive current collector;
[0007] The positive electrode film layer includes a composite positive electrode active material; the composite positive electrode active material includes a core layer and a shell layer from the inside to the outside.
[0008] The core layer includes a positive electrode active material;
[0009] The shell consists of a first shell, a second shell, and a third shell in sequence along the direction away from the core layer;
[0010] The first shell layer has a rock salt phase structure;
[0011] The second shell comprises sulfates and / or sulfites;
[0012] The third shell comprises elemental sulfur.
[0013] In the technical solution of this application, the composite positive electrode active material is used to form the positive electrode sheet, which is beneficial to improving the cycle performance of the battery cell under high pressure. Specifically, the first shell layer basically does not deintercalate or intercalate active ions, and has the characteristics of small strain and high mechanical strength under high pressure, which can improve the cycle performance of the battery cell under high pressure. The second shell layer has the advantages of stable thermodynamic properties and high conductivity; the third shell layer can be oxidized to form sulfite or sulfate during high pressure cycling, which has good active ion transport capacity, migrates to the negative electrode surface or remains on the positive electrode surface, and can suppress the deterioration of cycling kinetics. Moreover, the non-polar properties of elemental sulfur make it hydrophobic, which can improve the moisture resistance of the composite positive electrode active material, reduce the adverse effects of moisture on the performance of the battery cell, and improve the cycle performance of the battery cell under high pressure. Therefore, the positive electrode active material of this application, through the mutual cooperation of the above three-layer structure, can reduce the lattice expansion inside the material during the active ion deintercalation and intercalation process and suppress the dissolution of transition metals in the positive electrode active material, which can improve the cycle performance of the battery cell under high pressure. In addition, the composite positive electrode active material with the above structure, compared with the positive electrode active material without a first shell, second shell or third shell, can reduce the alkalinity of the material surface, improve the gelation phenomenon, and further optimize the cycle performance of the battery cell, especially the cycle performance under high voltage.
[0014] In some embodiments, the positive electrode active material includes a ternary positive electrode material;
[0015] The structural formula of the ternary cathode material is LiNi. x Co y N 1-x-y O2, wherein N includes at least one of Mn, Al, B, Mo, Zr, Ta, W, Nb, La, and Sb, and 0.35 ≤ x < 1, 0 ≤ y < 0.35, and 0 ≤ 1 - xy < 0.35.
[0016] In some implementations, ternary cathode materials are widely applicable active materials. Using them as the core layer in conjunction with the shell layer, the resulting battery cell not only meets basic electrochemical performance requirements but also exhibits excellent cycle performance under high voltage.
[0017] In some embodiments, the first shell layer comprises a material with a rock salt phase structure;
[0018] The chemical formula of the rock salt phase structure material is Ni. a Co b N 1-a-b O 1.5 Wherein, N includes at least one of Mn, Al, B, Mo, Zr, Ta, W, Nb, La, and Sb, and 0.35≤a≤1, 0≤b<0.35, and 0≤1-ab<0.35.
[0019] In the technical solution of this application, the rock salt phase structure is a typical cubic crystal system structure. The first shell of the rock salt phase structure has high structural stability and good ion transport performance, which can improve the cycle performance of the battery cell, especially the cycle performance under high voltage.
[0020] In some embodiments, the thickness of the first shell layer is 3 to 6 nm.
[0021] In the technical solution of this application, the thickness of the first shell layer is within the above-mentioned range. On the basis of excellent structural stability, the transport channels of active ions are also appropriate, and the impact on the internal resistance of the battery is small. That is, the thickness of the first shell layer within the above-mentioned range improves the cycle performance of the battery cell and has little adverse effect on the electrochemical performance of the battery cell, resulting in better overall performance of the battery cell.
[0022] In some embodiments, the mass content of the second shell layer is 0.25% to 0.7% based on the mass of the composite positive electrode active material as 100%.
[0023] In the technical solution of this application, the mass content of the second shell layer is within the above range, and it cooperates well with the core layer, the first shell layer or the third shell layer, which can optimize the cycle performance of the battery cell under high voltage.
[0024] In some embodiments, in the positive electrode active material, 0.7 ≤ x < 0.8, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.25% to 0.5%; and / or;
[0025] In the positive electrode active material, 0.8 ≤ x < 0.9, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.35% to 0.6%; and / or;
[0026] In the positive electrode active material, 0.9 ≤ x < 1, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.45% to 0.7%.
[0027] In the technical solution of this application, the mass content of ternary cathode materials with different Ni element contents is within the above-mentioned range. The mass content of different ternary cathode materials in the composite cathode active material is within different ranges. The core layer and the second shell layer can cooperate better, further optimizing the cycle performance of the battery cell under high voltage.
[0028] In some embodiments, the mass content of the third shell layer is 0.02% to 0.2% based on the mass of the composite positive electrode active material being 100%.
[0029] In the technical solution of this application, the mass content of the third shell layer is within the above range, and it cooperates well with the core layer, the first shell layer or the second shell layer, which can optimize the cycle performance of the battery cell under high voltage.
[0030] In some embodiments, the average particle size of the composite positive electrode active material is 2 to 4 μm.
[0031] In the technical solution of this application, the average particle size of the composite positive electrode active material is within the above range, which can balance the reduction of impedance and the reduction of side reactions with the electrolyte, resulting in better overall performance of the battery cell, such as cycle performance, especially cycle performance under high voltage.
[0032] In some embodiments, the specific surface area of the composite positive electrode active material is 0.8–1.5 m². 2 / g.
[0033] In the technical solution of this application, the specific surface area of the composite positive electrode active material is within the above-mentioned range, which is beneficial for contact with the electrolyte, reduces the increase of material surface impedance, and can optimize the overall performance of the battery cell, such as cycle performance, especially cycle performance under high voltage.
[0034] In some embodiments, the sulfur content is 0.01% to 0.5% by mass, based on 100% of the composite positive electrode active material.
[0035] In the technical solution of this application, the mass content of sulfur in the composite positive electrode active material is within the above-mentioned range, which is beneficial to improve the dynamic performance of the battery cell and improve its cycle performance, especially the cycle performance under high voltage.
[0036] Secondly, this application provides a method for preparing a composite positive electrode active material, the method comprising the following steps:
[0037] The positive electrode active material and elemental sulfur are mixed and sublimed under reduced pressure to obtain the composite positive electrode active material.
[0038] The composite positive electrode active material comprises a core layer and a shell layer from the inside out;
[0039] The core layer includes a positive electrode active material;
[0040] The shell consists of a first shell, a second shell, and a third shell in sequence along the direction away from the core layer;
[0041] The first shell layer has a rock salt phase structure;
[0042] The second shell comprises lithium sulfate and / or lithium sulfite;
[0043] The third shell comprises elemental sulfur.
[0044] In some embodiments, the temperature of the reduced pressure sublimation is 60–100°C; and / or;
[0045] The time for the decompression sublimation is 0.1-1 h.
[0046] Thirdly, this application provides a battery device comprising a plurality of battery cells according to the first aspect.
[0047] Fourthly, this application provides an electrical device comprising the battery cell described in the first aspect, or the composite positive electrode active material obtained by the preparation method described in the second aspect, or the battery device described in the fourth aspect.
[0048] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0049] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0050] Figure 1 This is a schematic diagram of one embodiment of the battery cell of this application;
[0051] Figure 2 This is a transmission electron microscope (TEM) schematic diagram of the composite positive electrode active material of some embodiments of this application;
[0052] Figure 3 A schematic diagram of one embodiment of an electrical device that uses the battery device of this application as a power source;
[0053] Figure 4 This is a schematic diagram of the structure of the composite positive electrode active material in some embodiments of this application;
[0054] The reference numerals in the detailed embodiments are as follows:
[0055] 1-Core layer; 2-First shell layer; 3-Second shell layer; 4-Third shell layer; 5-Amorphous phase. Detailed Implementation
[0056] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0058] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0059] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0060] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it is also expected that ranges of 60–110 and 80–120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "2-10" indicates that all real numbers between "2-10" have been listed in this article; "2-10" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0061] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent three cases: A exists, A and B exist simultaneously, and B exists. In addition, the character " / " in this document generally indicates that the related objects before and after it have an "or" relationship.
[0062] Some active materials in certain systems, such as ternary cathode active materials, exhibit poor cycle performance under high voltage conditions, which limits the application of battery cells. Therefore, it is crucial to provide a battery cell with excellent cycle performance under high voltage.
[0063] [Battery cell]
[0064] In this embodiment of the application, the battery cell can be a secondary battery, which refers to a battery cell that can be used again after being discharged by recharging to activate the active materials. Figure 1 A schematic diagram of one embodiment of the battery cell of this application is provided as an example.
[0065] The battery cell can be a lithium-ion battery, sodium-ion battery, sodium-lithium-ion battery, lithium metal battery, sodium metal battery, lithium-sulfur battery, magnesium-ion battery, nickel-metal hydride battery, nickel-cadmium battery, lead-acid battery, etc., and the embodiments of this application are not limited to this.
[0066] [Electrode Assembly]
[0067] A single battery cell typically includes an electrode assembly. The electrode assembly includes a positive electrode, a negative electrode, and a separator, with the separator positioned between the negative and positive electrodes. During the charging and discharging process of a single battery cell, active ions (such as lithium ions or sodium ions) repeatedly insert and extract between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, prevents short circuits while allowing active ions to pass through.
[0068] The electrode assembly can be a wound structure, a stacked structure, or a hybrid structure of wound and stacked.
[0069] In some implementations, the electrode assembly is a wound structure. The positive and negative electrode sheets are wound into a wound structure.
[0070] In some implementations, the electrode assembly is a stacked structure.
[0071] As an example, multiple positive and negative electrode plates can be set, and multiple positive and multiple negative electrode plates can be stacked alternately.
[0072] As an example, multiple positive electrode sheets can be set, and negative electrode sheets are folded to form multiple stacked folded segments, with a positive electrode sheet sandwiched between adjacent folded segments.
[0073] As an example, both the positive and negative electrode sheets are folded to form multiple stacked folded segments.
[0074] In some embodiments, the electrode assembly can be cylindrical, flat, or polygonal, etc.
[0075] In some embodiments, the electrode assembly is provided with tabs that allow current to be drawn from the electrode assembly. The tabs include a positive tab and a negative tab.
[0076] [Positive electrode plate]
[0077] This application provides a battery cell, the battery cell including a positive electrode sheet;
[0078] The positive electrode includes a positive current collector and a positive film layer disposed on at least one surface of the positive current collector;
[0079] The positive electrode film layer includes a composite positive electrode active material; the composite positive electrode active material includes a core layer and a shell layer from the inside to the outside.
[0080] The core layer includes a positive electrode active material;
[0081] The shell consists of a first shell, a second shell, and a third shell in sequence along the direction away from the core layer;
[0082] The first shell layer has a rock salt phase structure;
[0083] The second shell comprises sulfates and / or sulfites;
[0084] The third shell comprises elemental sulfur.
[0085] In this application, the composite positive electrode active material of the battery cell can be determined by the following method:
[0086] (1) Structure determination: The structure of the composite positive electrode active material was observed and analyzed using an electron microscope (such as a ZEISS transmission electron microscope TEM), as follows:
[0087] 1) Sample preparation: Disassemble the battery cell, peel off the positive electrode film layer on the surface of the positive electrode sheet, obtain the composite positive electrode active material by scraping and gravity screening with a cyclone separator, select a suitable support film (e.g., copper foil), and disperse the composite positive electrode active material in a dispersant (e.g., anhydrous ethanol) using ultrasound or stirring; drop the dispersion onto the support film, and after drying, it can be observed by TEM.
[0088] 2) Place the prepared sample on the TEM sample holder, ensuring that the sample is in the electron beam path. Adjust parameters such as accelerating voltage and magnification, observe the microstructure of the sample through TEM, and record images and data.
[0089] 3) The analyzed image shows that the innermost layer is the core layer (e.g., a layered structure), the rock salt phase structure on its surface is the first shell layer, and the outer structure is an amorphous phase layer composed of a second and third shell layers. Since the second and third shell layers have similar compositions, a clear boundary may not be visible in the electron microscope image. For example, the transmission electron microscope (TEM) scan of the positive electrode active material verified in this application is shown below. Figure 2 As shown, the composite positive electrode active material consists of a core layer 1 from the inside out, exhibiting a layered structure; the outer side of the core layer is the first shell layer 2 of rock salt phase, whose thickness or microstructure can be observed and analyzed using multiple regions such as region I and region II; the outer side of the first shell layer is an amorphous phase 5 structure, which is the second and third shell layers. The second and third shell layers have similar material compositions and the boundary between the layers is not obvious.
[0090] (2) Determination of the material in each layer:
[0091] After disassembling the battery cell, the positive electrode sheet is obtained. The positive electrode film layer is peeled off to obtain the composite positive electrode active material. First, an inductively coupled plasma (ICP) tester (model Hengmei) is used to test whether sulfur is present in the amorphous phase layer. If it is present, the composite positive electrode active material is immersed in carbon disulfide (CS2) solvent (sulfur is only soluble in CS2, which is nonpolar and does not dissolve other substances, while elemental sulfur is soluble in the solvent). Then, TEM is performed to observe whether there is an amorphous phase layer, or whether it is thinned or its morphology changes. If so, it is determined that elemental sulfur is present in the outermost layer, i.e., the third shell layer. Then, the composition of the remaining second shell layer is tested by electrochemical titration.
[0092] In the technical solution of this application embodiment, the positive electrode sheet is formed using the above-mentioned composite positive electrode active material, which is beneficial to improving the cycle performance of the battery cell under high voltage. Specifically, the first shell layer basically does not deintercalate or intercalate active ions, and has the characteristics of small strain and high mechanical strength under high voltage, which can improve the cycle performance of the battery cell under high voltage. The second shell layer has the advantages of stable thermodynamic properties and high conductivity; the third shell layer can be oxidized to form sulfite or sulfate during high voltage cycling, which has good active ion transport capacity, migrating to the negative electrode surface or remaining on the positive electrode surface, which can suppress the deterioration of cycling kinetics. Moreover, the non-polar properties of elemental sulfur make it hydrophobic, which can improve the moisture resistance of the composite positive electrode active material, reduce the adverse effects of moisture on the performance of the battery cell, and improve the cycle performance of the battery cell under high voltage. Therefore, the positive electrode active material of this application, through the mutual cooperation of the above three-layer structure, can reduce the lattice expansion inside the material during the active ion deintercalation and intercalation process and suppress the dissolution of transition metals in the positive electrode active material, which can improve the cycle performance of the battery cell under high voltage. In addition, the composite positive electrode active material with the above structure, compared with the positive electrode active material without a first shell, second shell or third shell, can reduce the alkalinity of the material surface, improve the gelation phenomenon, and further optimize the cycle performance of the battery cell, especially the cycle performance under high voltage.
[0093] In some embodiments, the positive electrode active material includes a first, a second, and a third ternary positive electrode material.
[0094] In this application, the general structural formula of the ternary cathode material can be LiNi. x Co y N 1-x-y O2, wherein N includes at least one of Mn, Al, B, Mo, Zr, Ta, W, Nb, La, and Sb, and 0.35 ≤ x < 1 (e.g., 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, etc.), 0 ≤ y < 0.35 (e.g., 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, etc.), and 0 ≤ 1 - xy < 0.35 (e.g., 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, etc.).
[0095] This application does not limit the types of ternary cathode materials. Depending on the nickel content, ternary cathode materials can be low-nickel ternary cathode materials, medium-nickel ternary cathode materials, and high-nickel ternary cathode materials. Specifically, the first ternary cathode material refers to a ternary cathode material in which the molar content of nickel relative to the transition metal element is greater than or equal to 70% and less than 80%; the second ternary cathode material refers to a ternary cathode material in which the molar content of nickel relative to the transition metal element is greater than or equal to 80% and less than 90%; and the third ternary cathode material refers to a ternary cathode material in which the molar content of nickel relative to the transition metal element is greater than or equal to 90%.
[0096] In some embodiments, ternary cathode materials are widely applicable active materials. Using them as the core layer in conjunction with the shell layer, the resulting battery cell not only meets basic electrochemical performance requirements but also exhibits excellent cycle performance under high voltage.
[0097] In some embodiments, the first shell layer comprises a material with a rock salt phase structure;
[0098] The chemical formula of the rock salt phase structure material is Ni. a Co b N 1-a-b O 1.5 Wherein, N includes at least one of Mn, Al, B, Mo, Zr, Ta, W, Nb, La, and Sb, 0.35≤a≤1 (e.g., 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, etc.), 0≤b<0.35 (e.g., 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, etc.), and 0≤1-ab<0.35 (e.g., 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, etc.).
[0099] In the technical solution of this application embodiment, the rock salt phase structure is a typical cubic crystal system structure. The first shell of the rock salt phase structure has high structural stability and good ion transport performance. During the cycling process, the insertion and extraction of active ions exhibits isotropic structural changes, that is, the lattice changes in all directions are relatively uniform. Therefore, the first shell can effectively reduce mechanical stress and structural fatigue, thereby improving the cycle performance of the battery cell, especially the cycle performance under high voltage.
[0100] In some embodiments, the thickness of the first shell layer is 3 to 6 μm, such as 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, etc.
[0101] In this application, the method for testing the thickness of the first shell is not limited, and any method known in the art can be used. For example, the thickness of the first shell can be measured by directly observing the interface of the core-shell structure using a ZEISS TEM.
[0102] In the technical solution of this application embodiment, the thickness of the first shell layer is within the above-mentioned range. On the basis of excellent structural stability, the transport channels of active ions are also appropriate, and the impact on the internal resistance of the battery is small. That is, the thickness of the first shell layer within the above-mentioned range improves the cycle performance of the battery cell and has little adverse impact on the electrochemical performance of the battery cell, resulting in better overall performance of the battery cell.
[0103] In this application, the mass percentage of the first shell in the composite positive electrode active material can be obtained through simple reasoning. The first shell has a rock salt phase structure, and based on its density, particle size, and thickness, empirically, its density is estimated to be 2.4 g / cm³. 3 If the median particle size is 3 μm and the thickness is 3-6 nm, then the volume of the first shell is 0.17 × 10⁻⁶. -12 ~0.85×10 - 12 cm 3 The mass range of the first shell is 0.41 × 10⁻⁶. -12 ~2×10 -12 g, the mass proportion in the composite positive electrode active material ranges from 0.6% to 2.8%.
[0104] In some embodiments, based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.25% to 0.7%, for example, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, etc.
[0105] In the technical solution of this application embodiment, the mass content of the second shell layer is within the above range, and its interaction with the core layer, the first shell layer or the third shell layer is good, which can optimize the cycle performance of the battery cell under high voltage.
[0106] In some embodiments, the positive electrode active material is selected from a first ternary positive electrode material, that is, in the positive electrode active material, 0.7≤x<0.8, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.25% to 0.5%, for example 0.3%, 0.35%, 0.4%, 0.45%, etc.; and / or;
[0107] The positive electrode active material is selected from a second ternary positive electrode material, that is, in the positive electrode active material, 0.8≤x<0.9, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.35% to 0.6%, for example 0.4%, 0.45%, 0.5%, 0.55%, etc.; and / or;
[0108] The positive electrode active material is selected from the third ternary positive electrode material, that is, in the positive electrode active material, 0.9≤x<1, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.45% to 0.7%, for example 0.5%, 0.55%, 0.6%, 0.65%, etc.
[0109] In the technical solutions of this application embodiment, the mass content of ternary cathode materials (first, second, and third ternary cathode materials) with different Ni element contents are each within the above-mentioned range. Different ternary cathode materials have different mass contents in the composite cathode active material, allowing the core layer and the second shell layer to work together better, further optimizing the cycle performance of the battery cell under high voltage. In some embodiments, based on the mass of the composite cathode active material as 100%, the mass content of the third shell layer is 0.02% to 0.2%, for example, 0.05%, 0.1%, 0.15%, etc.
[0110] In this application, the testing method for the mass content of each layer is not limited, and any method known in the art can be used. For example, after disassembling the battery cell to obtain the positive electrode sheet, the positive electrode film layer is peeled off to obtain a certain mass of composite positive electrode active material, and it is immersed in carbon disulfide (CS2) solvent (sulfur is only soluble in CS2, and CS2 is non-polar and does not dissolve other substances). The elemental sulfur in the third shell layer is soluble in the solvent, while the sulfate or sulfite in the second shell layer is not soluble. Quantitative analysis is performed to obtain the mass content of the third shell layer in the composite positive electrode active material.
[0111] Furthermore, the sulfur content of the composite positive electrode active material after the third shell is dissolved is tested using an inductively coupled plasma (ICP) instrument (model Hengmei), and the mass content of sulfate or sulfite is inferred. For the first shell, the size ratio of the core layer and the first shell is observed by TEM, and the mass content of the second and third shells is referenced to quantitatively analyze the mass content of the first shell in the composite positive electrode active material.
[0112] In the technical solution of this application embodiment, the mass content of the third shell layer is within the above range, and its interaction with the core layer, the first shell layer or the second shell layer is good, which can optimize the cycle performance of the battery cell under high voltage.
[0113] In this application, the thickness of the second and third shells corresponds to their respective mass content. For example, the thickness of the second shell is determined by its mass content in the composite active material. Its thickness can be characterized by instruments or estimated based on its mass content in the composite active material. Specifically, its thickness is related to the true density of the positive electrode active material in the second shell and the core layer, as well as the average particle size. For example, the true density of the second shell is 2 g / cm³. 3 The true density of the positive electrode active material is 5 g / cm³. 3 The average particle size is 3 μm. Based on the density and mass ratios, the thickness of the second shell can be 3–8.4 nm. Further, the positive electrode active material is selected from a first ternary positive electrode material with a thickness of 3–6 nm, a second ternary positive electrode material with a thickness of 4.2–7.2 nm, and a third ternary positive electrode material with a thickness of 5.4–8.4 nm. These ranges are illustrative and do not imply a limitation on the thickness. Similarly, the thickness of the third shell can be initially analyzed based on the above principles, or further calculated based on the thickness of the amorphous phase observed under an electron microscope and the aforementioned thickness of the second shell. This will not be elaborated upon here. For example, based on the foregoing description, the thickness of the third shell can be 0.6–2.5 nm. Again, this is merely illustrative and does not constitute a limitation on the thickness of the third shell.
[0114] In some embodiments, the average particle size of the composite positive electrode active material is 2 to 4 μm, such as 2.5 μm, 3 μm, 3.5 μm, etc.
[0115] In this application, the average particle size refers to the median particle size, or Dv50 particle size, which is the particle size corresponding to 50% of the cumulative distribution in the volume distribution of particles. This application does not limit the testing method for the average particle size; any method known in the art can be used, such as laser particle size analysis or electron microscopy.
[0116] In the technical solution of this application embodiment, the average particle size of the composite positive electrode active material is within the above range, which can balance the relationship between reducing impedance and reducing side reactions with electrolyte, and the overall performance of the battery cell, such as cycle performance, especially cycle performance under high voltage, is better.
[0117] In some embodiments, the specific surface area of the composite positive electrode active material is 0.8–1.5 m². 2 / g, for example 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g etc.
[0118] In this application, specific surface area refers to the total surface area of a unit mass of solid material; this application does not limit the test method for specific surface area, and any method known in the art can be used, such as the gas adsorption method (BET method).
[0119] In the technical solution of this application embodiment, the specific surface area of the composite positive electrode active material is within the above-mentioned range, which is beneficial for contact with the electrolyte, reduces the increase of material surface impedance, and can optimize the comprehensive performance of the battery cell, such as cycle performance, especially cycle performance under high voltage.
[0120] In some embodiments, the mass content of sulfur element is 0.01% to 0.5% based on the mass of the composite positive electrode active material as 100%, for example, 0.1%, 0.2%, 0.3%, 0.4%, etc.
[0121] In this application, the method for testing the mass content of sulfur is not limited, and methods known in the art can be used, such as the aforementioned method for determining the mass content of the shell, which will not be elaborated here.
[0122] In the technical solution of this application embodiment, the mass content of sulfur in the composite positive electrode active material is within the above range, which is beneficial to improve the dynamic performance of the battery cell and improve its cycle performance, especially the cycle performance under high voltage.
[0123] In this application, the sulfur element in the negative electrode mainly comes from the third shell of the composite positive electrode active material. After the newly prepared composite positive electrode active material is made into a battery cell and is put into actual operation, the elemental sulfur is partially dispersed into the electrolyte and migrates to the negative electrode to be reduced to form a polymer solid electrolyte (SEI) film.
[0124] In some embodiments, the positive electrode film layer further includes a conductive agent and / or a binder.
[0125] As an example, the conductive agent includes one or more of carbon black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0126] As an example, the carbon black includes one or more of acetylene black, Ketjen black, or Super P.
[0127] As an example, the adhesive includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorinated acrylate resin.
[0128] [Preparation of Composite Positive Electrode Active Materials]
[0129] In some embodiments, this application provides a method for preparing a composite positive electrode active material, the method comprising the following steps:
[0130] The positive electrode active material and elemental sulfur are mixed and sublimed under reduced pressure to obtain the composite positive electrode active material.
[0131] The composite positive electrode active material comprises a core layer and a shell layer from the inside out;
[0132] The core layer includes a positive electrode active material;
[0133] The shell consists of a first shell, a second shell, and a third shell in sequence along the direction away from the core layer;
[0134] The first shell layer has a rock salt phase structure;
[0135] The second shell comprises lithium sulfate and / or lithium sulfite;
[0136] The third shell comprises elemental sulfur.
[0137] In the technical solution of this application embodiment, some positive electrode active materials, such as ternary positive electrode materials, inevitably form surface residual alkali (LiOH, Li2CO3, etc.) during synthesis and storage. These residual alkalis are mixed with excess elemental sulfur in a vacuum sublimation device at a chemical mass ratio. Some of the sulfur reacts with air to convert into SO2, and reacts with the surface residual alkali to convert into Li2SO3 and / or Li2SO4. The excess SO2 reacts with the active lithium in the surface positive electrode active material to form Li2SO3 and / or Li2SO4, forming a second shell. The surface of the positive electrode active material after the reaction is the first shell. Another part of the sublimated sulfur is uniformly deposited on the surface of the second shell to form a third shell, thus obtaining the above-mentioned composite positive electrode active material.
[0138] In some embodiments, the mass ratio of ternary cathode material to elemental sulfur can be 1:(0.005-0.1), where 0.005-0.1 can be 0.01, 0.02, 0.04, 0.06, 0.08, etc.
[0139] In some embodiments, the temperature of the reduced pressure sublimation is 60–100°C, for example, 75°C, 80°C, 85°C, 90°C, 95°C, etc.; and / or;
[0140] The time for the decompression sublimation is 0.1-1h, for example, 0.2h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, etc.
[0141] In this application, the initial state of the composite positive electrode active material prepared by the above method is as follows: it includes a core layer and a shell layer from the inside to the outside; the core layer includes the positive electrode active material; the shell layer includes a first shell layer, a second shell layer and a third shell layer in sequence along the direction away from the core layer.
[0142] The positive electrode active material can be selected from ternary positive electrode materials, and can be a first ternary positive electrode material, a second ternary positive electrode material, or a third ternary positive electrode material.
[0143] The first shell is a rock salt phase, and its thickness is 3–6 μm, based on the mass of the composite positive electrode active material as 100%.
[0144] The second shell layer comprises sulfates and / or sulfites, and its mass content is 0.25% to 0.7% based on 100% of the composite positive electrode active material.
[0145] Furthermore, the positive electrode active material is selected from the first ternary positive electrode material, and the mass content of the second shell layer is 0.25% to 0.5% based on the mass of the composite positive electrode active material as 100%; and / or;
[0146] The positive electrode active material is selected from second-stage ternary positive electrode materials, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.35% to 0.6%; and / or;
[0147] The positive electrode active material is selected from the third ternary positive electrode material. Based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.45% to 0.7%.
[0148] The third shell, which includes elemental sulfur, has a mass content of 0.03% to 0.2% based on the mass of the composite positive electrode active material as 100%.
[0149] The composite positive electrode active material has an average particle size of 2–4 μm and a specific surface area of 0.8–1.5 m². 2 / g.
[0150] Based on the mass of the composite positive electrode active material as 100%, the mass content of sulfur element is 0.01% to 0.5%.
[0151] After the composite positive electrode active material is formed into a battery cell, the stable state after cycling is as follows: it includes a core layer and a shell layer from the inside to the outside; the core layer includes the positive electrode active material; the shell layer includes a first shell layer, a second shell layer and a third shell layer in sequence along the direction away from the core layer, mainly the outermost third shell layer, which has a reduced content due to its participation in SEI film loss.
[0152] The positive electrode active material can be selected from ternary positive electrode materials, and can be a first ternary positive electrode material, a second ternary positive electrode material, or a third ternary positive electrode material.
[0153] The first shell is a rock salt phase, and its thickness is 3–6 μm, based on the mass of the composite positive electrode active material as 100%.
[0154] The second shell layer comprises sulfates and / or sulfites, and its mass content is 0.25% to 0.7% based on 100% of the composite positive electrode active material.
[0155] Furthermore, the positive electrode active material is selected from the first ternary positive electrode material, and the mass content of the second shell layer is 0.25% to 0.5% based on the mass of the composite positive electrode active material as 100%; and / or;
[0156] The positive electrode active material is selected from second-stage ternary positive electrode materials, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.35% to 0.6%; and / or;
[0157] The positive electrode active material is selected from the third ternary positive electrode material. Based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.45% to 0.7%.
[0158] The third shell, which includes elemental sulfur, has a mass content of 0.02% to 0.1% based on the mass of the composite positive electrode active material as 100%.
[0159] The composite positive electrode active material has an average particle size of 2–4 μm and a specific surface area of 0.8–1.5 m². 2 / g.
[0160] Based on the mass of the composite positive electrode active material as 100%, the mass content of sulfur element is 0.01% to 0.5%.
[0161] [Preparation of the positive electrode sheet]
[0162] In some embodiments, a negative electrode material, such as a composite positive electrode active material, a conductive agent (e.g., carbon black), a binder (e.g., polyvinylidene fluoride PVDF), and other arbitrary components (e.g., dispersants) are dissolved in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated onto the surface of a positive electrode composite current collector (e.g., aluminum foil) to form a positive electrode film layer, and then dried, cold-pressed, and die-cut to obtain a positive electrode sheet.
[0163] [Negative electrode plate]
[0164] In some embodiments, the negative electrode may be a negative electrode sheet, which includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface (e.g., one or two) of the negative electrode current collector.
[0165] As an example, the negative electrode current collector can be a metal foil, a conductive polymer material, a carbon material, or a composite current collector. For example, as a metal foil, pure metals, alloys, or surface-treated metals can be used, including but not limited to stainless steel, copper, aluminum, nickel, titanium, or silver. The composite current collector may include a polymer material substrate and a metal layer. The composite current collector can be formed by forming a metal material (copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).
[0166] In some embodiments, the negative electrode film layer comprises a negative electrode active material.
[0167] As an example, the negative electrode active material may be a negative electrode active material known in the art for use in battery cells. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for battery cells may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0168] In some embodiments, the negative electrode can be a foamed metal. The foamed metal can be foamed nickel, foamed copper, foamed aluminum, foamed alloy, or foamed carbon, etc. When foamed metal is used as the negative electrode sheet, the surface of the foamed metal may or may not have a negative electrode active material.
[0169] As an example, negative electrode active materials can be filled or / and deposited within the negative electrode current collector.
[0170] In some embodiments, the positive current collector can be made of aluminum, and the negative current collector can be made of copper.
[0171] [Preparation of the negative electrode sheet]
[0172] In some embodiments, a negative electrode material, such as a negative electrode active material (e.g., graphite), a conductive agent (e.g., carbon black), a binder (e.g., styrene-butadiene rubber), and other arbitrary components (e.g., dispersants, thickeners, etc.) are dissolved in a solvent (e.g., water) to form a negative electrode slurry; the negative electrode slurry is coated onto the surface of a negative electrode composite current collector (e.g., copper foil) to form a negative electrode film layer, and then dried, cold-pressed, and die-cut to obtain a negative electrode sheet.
[0173] [Isolation Component]
[0174] In some embodiments, the battery cell further includes a separator disposed between the positive electrode and the negative electrode.
[0175] As an example, multiple separators can be provided, each positioned between any adjacent positive or negative electrode plates.
[0176] As an example, the separator can be set continuously, either by folding or rolling between any adjacent positive or negative electrode plates.
[0177] In some embodiments, the separator is a separator membrane. This application does not impose any particular limitation on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0178] As an example, the main material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and ceramic. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation. The separator can be a single component located between the positive and negative electrodes, or it can be attached to the surfaces of the positive and negative electrodes. An inorganic particle coating, an organic particle coating, or an organic / inorganic composite coating can also be applied to the surface of the separator.
[0179] In some embodiments, the separator is a solid electrolyte. The solid electrolyte is disposed between the positive and negative electrode plates, serving both to transport ions and to isolate the positive and negative electrodes.
[0180] [Electrolytes]
[0181] In some embodiments, the battery cell further includes an electrolyte. The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte, which can be selected according to requirements. The electrolyte can be liquid, gel, or solid.
[0182] Liquid electrolytes include electrolyte salts and solvents.
[0183] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0184] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone. The solvent may also be an ether solvent. Ether solvents may include one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyl tetrahydrofuran, diphenyl ether, and crown ethers.
[0185] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the battery cell, such as additives that improve the overcharge / fast charge performance of the battery cell, additives that improve the high-temperature performance of the battery cell, and additives that improve the low-temperature performance of the battery cell.
[0186] The gel electrolyte includes a polymer as a backbone network and can be used in conjunction with an ionic liquid-lithium salt.
[0187] Solid electrolytes include polymer solid electrolytes, inorganic solid electrolytes, and composite solid electrolytes.
[0188] As an example, the polymers of polymeric solid electrolytes may include polyethers (polyoxyethylene), polysiloxanes, polycarbonates, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, monoionic polymers, polyionic liquids, cellulose, etc.
[0189] As an example, inorganic solid electrolytes can be one or more of the following: oxide solid electrolytes (crystalline perovskite, sodium superconducting ion conductor, garnet, amorphous LiPON thin film), sulfide solid electrolytes (crystalline lithium superconducting ion conductor (lithium germanium phosphorus sulfide, silver sulfide germanium ore), amorphous sulfides), halide solid electrolytes, nitride solid electrolytes, and hydride solid electrolytes.
[0190] As an example, composite solid electrolytes are formed by adding inorganic solid electrolyte fillers to polymer solid electrolytes.
[0191] [Battery Device]
[0192] In some embodiments, a battery cell may include a casing. The casing may be a steel casing, an aluminum casing, a plastic casing (such as a polypropylene casing), a composite metal casing (such as a copper-aluminum composite casing), or an aluminum-plastic film, etc. In some embodiments, the casing may be a sealed structure or a non-sealed structure. As an example, when the casing is a non-sealed structure, the casing serves to protect the electrode assembly, and a sealing bag is included between the casing and the electrode assembly to encapsulate the electrode assembly and electrolyte. Specifically, the sealing bag may be a bag-shaped insulating component or an aluminum-plastic film. When the casing is a sealed structure, it is used to encapsulate components such as the electrode assembly and electrolyte.
[0193] As an example, the battery cell can be a cylindrical battery cell, a prismatic battery cell, a pouch battery cell, or a battery cell of other shapes. Prismatic battery cells include prismatic battery cells, blade-shaped battery cells, and multi-prismatic batteries, such as hexagonal prismatic batteries. This application does not have any particular limitations.
[0194] In some embodiments, the housing includes an end cap and a housing, the housing having an opening, and the end cap covering the opening. The housing may have one or more openings. The end cap may also be provided one or more.
[0195] The battery apparatus mentioned in the embodiments of this application may include one or more battery cell assemblies for providing voltage and capacity. A battery cell assembly may include multiple battery cells connected in series, parallel, or mixed connections via a busbar.
[0196] In some embodiments, a battery cell assembly is typically formed by arranging multiple battery cells.
[0197] As an example, a battery cell assembly can be a battery module, which is formed by arranging and fixing multiple battery cells together to form an independent module. As another example, a battery module can be formed by bundling multiple battery cells together with cable ties.
[0198] In some embodiments, the battery device may be a battery pack, which includes a housing and one or more individual battery cells housed within the housing.
[0199] As an example, the battery cell assembly can be a battery module, which can be housed in a housing by fixing the battery module in the housing.
[0200] As an example, battery cell assemblies can also be housed in a housing by directly fixing multiple battery cells to the housing.
[0201] As an example, the enclosure may include a first enclosure and a second enclosure. The first enclosure and the second enclosure are fastened together to form a closed space inside the enclosure to house the individual battery cells. Here, "closed" refers to covering or closing, and can be either sealed or unsealed. The first enclosure may be a top cover or a bottom plate.
[0202] As an example, the enclosure may include a top cover, a frame, and a bottom plate. The top cover and bottom plate are connected to the frame, creating an enclosed space inside the enclosure to house the individual battery cells.
[0203] In some embodiments, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.
[0204] [ Electrical appliances ]
[0205] This application provides an electrical device, which includes the aforementioned battery cell.
[0206] In some embodiments, the electrical device includes at least one of the battery modules or battery packs provided in any embodiment of this application.
[0207] The battery cells, battery modules, or battery packs described in this application can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., including but not limited to these. Figure 3 An exemplary schematic diagram of one embodiment of an electrical device that uses the battery device of this application as a power source is provided.
[0208] [Example]
[0209] Example 1
[0210] Positive electrode sheet:
[0211] (1) Preparation of composite positive electrode active materials:
[0212] 1) Using Ni 0.7 Co 0.05 Mn 0.25Using (OH)₂ as a precursor and Li₂CO₃ as the lithium salt, with a lithium ratio (molar ratio of Li to other metals) of 1.05, and Zr as a dopant, the mixture was sintered at 870℃ in an oxygen atmosphere with a doping concentration of 3000 ppm. After sintering, the sample was pulverized and then subjected to a second sintering coating, coating with 2000 ppm Al and 2000 ppm Co. The Al source was nano-sized alumina, and the Co source was nano-sized cobalt hydroxide. The mixture was sintered at 400℃ in an oxygen atmosphere for 8 hours, then pulverized to obtain the first ternary cathode material.
[0213] 2) The first ternary cathode material is mixed with excess elemental sulfur and subjected to reduced pressure sublimation (material temperature maintained at 80℃ for 0.5h) to obtain a composite cathode active material, the structural schematic of which is shown in the figure. Figure 4 As shown, the composite positive electrode active material comprises a core layer 1 and a shell layer from the inside out; the core layer includes the positive electrode active material; the shell layer, along the direction away from the core layer, comprises a first shell layer 2, a second shell layer 3, and a third shell layer 4; the second shell layer comprises lithium sulfate and lithium sulfite; the third shell layer comprises elemental sulfur. The thickness of the first shell layer and the mass content of the second and third shell layers are controlled by the time of depressurized sublimation. Its average particle size is 3 μm, and its specific surface area is 1.2 m². 2 / g.
[0214] (2) Preparation of positive electrode sheet: The composite positive electrode active material, conductive agent carbon black and binder polyvinylidene fluoride (PVDF) are dispersed in solvent NMP in a ratio of 97:2:1 and stirred and mixed evenly to obtain positive electrode slurry; then the positive electrode slurry is uniformly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed and cut to obtain positive electrode sheet.
[0215] Negative electrode sheet: The negative electrode active material artificial graphite, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water at a weight ratio of 96.2:0.8:0.8:1.2 and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then dried, cold-pressed, and slit to obtain the negative electrode sheet.
[0216] Electrolyte: In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate (EC) / ethyl methyl carbonate (EMC) organic solvents are mixed evenly at a volume ratio of 3 / 7. 12.5wt% lithium hexafluorophosphate (LiPF6) is added and dissolved in the organic solvent and stirred evenly to obtain the electrolyte.
[0217] Separating membrane: Polyethylene film is used as the separating membrane.
[0218] Assembly: The positive electrode sheet, separator, negative electrode sheet, separator and positive electrode sheet are stacked and wound in sequence to obtain the battery cell; then the positive and negative electrode tabs are ultrasonically welded, with aluminum tabs for the positive electrode and copper tabs for the negative electrode, and the positive and negative electrode tabs are located on the same side of the battery cell; the battery cell with the tabs welded is put into an aluminum shell for soft connection and top cover welding, the battery cell is vacuum dried at 110°C for 12 hours, and then liquid injection, standing, formation, degassing, and second sealing processes are performed to obtain the battery cell.
[0219] Examples 2-5 and Comparative Example 1
[0220] Except for the parameters in Table 1, the composite positive electrode active material was prepared according to the method in Example 1.
[0221] Table 1
[0222]
[0223] In the table, the mass content of sulfur refers to its mass content in the composite positive electrode active material, and the other similar expressions are expressed in the same way.
[0224] Example 6
[0225] The difference between this embodiment and Embodiment 1 is that the first ternary cathode material is replaced with a second ternary cathode material. Specifically, the preparation method of the second ternary cathode material includes the following steps:
[0226] Using Ni 0.83 Co 0.12 Mn 0.05 Using (OH)₂ as a precursor and Li₂CO₃ as the lithium salt with a lithium ratio of 1.05, Zr was selected as a dopant. After uniform mixing, the mixture was sintered at 870℃ in an oxygen atmosphere with a doping concentration of 3000 ppm. The sintered sample was then pulverized and subjected to a second sintering and coating process, coating with 2000 ppm Al and 2000 ppm Co. The Al source was nano-sized alumina, and the Co source was nano-sized cobalt hydroxide. Sintering was carried out at 400℃ in an oxygen atmosphere for 8 hours, followed by pulverization to obtain the second ternary cathode material. The resulting composite cathode active material was similar to that in Example 1, with the thickness of the first shell and the mass content of the second and third shells controlled by the time of depressurized sublimation. Its average particle size was 3 μm, and its specific surface area was 1.2 m². 2 / g.
[0227] Examples 7-8 and Comparative Example 2
[0228] Except for the parameters in Table 2, the composite positive electrode active material was prepared according to the method in Example 1.
[0229] Table 2
[0230]
[0231] Example 9
[0232] The difference between this embodiment and Embodiment 1 is that the first ternary cathode material is replaced with a third ternary cathode material. Specifically, the preparation method of the third ternary cathode material includes the following steps:
[0233] Using Ni 0.925 Co 0.06 Mn 0.015 Using (OH)₂ as a precursor and Li₂CO₃ as the lithium salt with a lithium ratio of 1.05, Zr was selected as a dopant. After uniform mixing, the mixture was sintered at 870℃ in an oxygen atmosphere with a doping amount of 3000 ppm. The sintered sample was then pulverized and subjected to a second sintering coating, coating with 2000 ppm Al and 2000 ppm Co. The Al source was nano-sized alumina, and the Co source was nano-sized cobalt hydroxide. Sintering was carried out at 400℃ in an oxygen atmosphere for 8 hours, followed by pulverization to obtain the third ternary cathode material. The resulting composite cathode active material was similar to that in Example 1, with the thickness of the first shell and the mass content of the second and third shells controlled by the time of depressurized sublimation. Its average particle size was 3 μm, and its specific surface area was 1.2 m². 2 / g.
[0234] Examples 10-11 and Comparative Example 3
[0235] Except for the parameters in Table 3, the composite positive electrode active material was prepared according to the method in Example 1.
[0236] Table 3
[0237]
[0238] Performance testing
[0239] (1) Retention rate after 1000 cycles:
[0240] First, the capacity of the battery cell is tested. The cell is left to stand at 25°C for 30 minutes, then charged at a constant rate of 0.33C to the upper limit voltage (4.4V for the first ternary cathode material / 4.25V for the second and third ternary cathode materials). After that, it is charged at a constant voltage to 0.05C, and then fully discharged at a constant rate of 0.33C to the lower limit voltage (2.5V). This cycle is repeated 3 times. The result of the third cycle is recorded as the actual capacity value, which is used as the initial capacity to determine the capacity.
[0241] At 25°C, after the hard-shell cell is fitted with a clamp and sensor, the capacity process described above is first performed. The cycle process is to charge at a constant rate of 0.33C to the upper limit voltage (4.4V for the first ternary cathode material / 4.25V for the second and third ternary cathode materials), and then discharge at a constant rate of 1C to the lower limit voltage (2.5V). This cycle is repeated 1000 times. The capacity after 1000 cycles is divided by the initial capacity to obtain the cycle retention rate after 1000 cycles.
[0242] (2) 30-day storage retention rate at 60℃: At 25℃, after the hard-shell cell is fitted with a clamp and sensor, the capacity process described in (1) is first performed. The cycle process is to charge at a constant rate of 0.33C to the upper limit voltage (4.4V for the first ternary cathode material / 4.25V for the second and third ternary cathode materials), and then stand at 60℃ for 30 days. Then discharge at a constant rate of 0.33C to the lower limit voltage (2.5V). Then charge and discharge again at 0.33C according to the above charge and discharge process for one cycle. The storage retention rate can be obtained by comparing the discharge capacity of the last cycle with the discharge capacity of the first cycle.
[0243] The test results are summarized in Table 4-6.
[0244] Table 4
[0245]
[0246] Table 4 shows some implementation methods using the first ternary cathode material as the core layer. Based on the analysis of Example 1 and Comparative Example 1, the battery cell formed by the composite cathode active material of this application has better performance.
[0247] Analysis of Examples 4-5 and Example 1 shows that the performance of Examples 4-5 is not as good as that of Example 1, proving that adjusting the thickness of the first shell layer within an appropriate range is more conducive to improving the cycle performance of the battery cell under high voltage.
[0248] Table 5
[0249]
[0250] Table 5 shows some implementation methods using the second ternary cathode material as the core layer. Based on the analysis of Example 6 and Comparative Example 2, the battery cell formed by the composite cathode active material of this application has better performance.
[0251] Table 6
[0252]
[0253] Table 6 shows some implementation methods using the third ternary cathode material as the core layer. Based on the analysis of Example 9 and Comparative Example 3, the battery cell formed by the composite cathode active material of this application has better performance.
[0254] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A battery cell, characterized in that, The battery cell includes a positive electrode sheet; The positive electrode includes a positive current collector and a positive film layer disposed on at least one surface of the positive current collector; The positive electrode film layer includes a composite positive electrode active material; the composite positive electrode active material includes a core layer and a shell layer from the inside to the outside. The core layer includes a positive electrode active material; The shell consists of a first shell, a second shell, and a third shell in sequence along the direction away from the core layer; The first shell layer has a rock salt phase structure; The second shell comprises sulfates and / or sulfites; The third shell comprises elemental sulfur.
2. The battery cell according to claim 1, characterized in that, The positive electrode active material includes a ternary positive electrode material; The structural formula of the ternary cathode material is LiNi. x Co y N 1-x-y O2, wherein N includes at least one of Mn, Al, B, Mo, Zr, Ta, W, Nb, La, and Sb, and 0.35 ≤ x < 1, 0 ≤ y < 0.35, and 0 ≤ 1 - xy < 0.
35.
3. The battery cell according to claim 1 or 2, characterized in that, The first shell layer comprises a material with a rock salt phase structure; The chemical formula of the rock salt phase structure material is Ni. a Co b N 1-a-b O 1.5 Wherein, N includes at least one of Mn, Al, B, Mo, Zr, Ta, W, Nb, La, and Sb, and 0.35≤a≤1, 0≤b<0.35, and 0≤1-ab<0.
35.
4. The battery cell according to any one of claims 1-3, characterized in that, The thickness of the first shell layer is 3–6 nm.
5. The battery cell according to any one of claims 1-4, characterized in that, Based on the mass of the composite positive electrode active material being 100%, the mass content of the second shell layer is 0.25% to 0.7%.
6. The battery cell according to any one of claims 2-5, characterized in that, In the positive electrode active material, 0.7 ≤ x < 0.8, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.25% to 0.5%; and / or; In the positive electrode active material, 0.8 ≤ x < 0.9, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.35% to 0.6%; and / or; In the positive electrode active material, 0.9 ≤ x < 1, and based on the mass of the composite positive electrode active material as 100%, the mass content of the second shell layer is 0.45% to 0.7%.
7. The battery cell according to any one of claims 1-6, characterized in that, Based on the mass of the composite positive electrode active material being 100%, the mass content of the third shell layer is 0.02% to 0.2%.
8. The battery cell according to any one of claims 1-7, characterized in that, The average particle size of the composite positive electrode active material is 2–4 μm.
9. The battery cell according to any one of claims 1-8, characterized in that, The specific surface area of the composite positive electrode active material is 0.8–1.5 m². 2 / g.
10. The battery cell according to any one of claims 1-9, characterized in that, Based on the mass of the composite positive electrode active material as 100%, the mass content of sulfur element is 0.01% to 0.5%.
11. A method for preparing a composite positive electrode active material, characterized in that, The preparation method includes the following steps: The composite positive electrode active material is obtained by mixing the positive electrode active material and elemental sulfur and then sublimating it under reduced pressure. The composite positive electrode active material comprises, from the inside out, a core layer and a shell layer; The core layer includes a positive electrode active material; The shell consists of a first shell, a second shell, and a third shell in sequence along the direction away from the core layer; The first shell layer has a rock salt phase structure; The second shell comprises lithium sulfate and / or lithium sulfite; The third shell comprises elemental sulfur.
12. The preparation method according to claim 11, characterized in that, The temperature for the vacuum sublimation is 60–100°C; and / or; The time for the decompression sublimation is 0.1-1 h.
13. A battery device, characterized in that, The battery device comprises a plurality of battery cells according to any one of claims 1-10.
14. An electrical appliance, characterized in that, The electrical device includes a battery cell according to any one of claims 1-10, or a composite positive electrode active material obtained by the preparation method according to claim 11 or 12, or a battery device according to claim 13.
